The language of design: Spatial cognition and spatial language in parametric design. (September 2016) - Lee, Ju Hyun; Ostwald, Michael J; Gu, Ning
This article develops a new research framework and method combining cognitive and linguistic approaches to investigate parametric design. At the core of this new approach is a dual-coding system for protocol analysis, which can formally capture both cognitive and linguistic characteristics of the design process. In this article, the method is applied to the analysis of the results of a design experimental undertaken by a set of Australian and Swedish architects working individually in a parametric environment. The results of the experiment demonstrate the effectiveness of the dual-coding system and, with the support of linkography, facilitate the in-depth exploration of design cognition and its relationship to spatial language. This method directly contributes to a new insight into the role of language in design.